Overview and critical revision of clinical assessment tools in chemotherapy‐induced peripheral neurotoxicity. (24th October 2019) - Park, Susanna B.; Alberti, Paola; Kolb, Noah A.; Gewandter, Jennifer S.; Schenone, Angelo; Argyriou, Andreas A.
Abstract: Chemotherapy‐induced peripheral neurotoxicity (CIPN) is a major toxicity of cancer treatment, leading to dose reduction and premature treatment cessation, potentially affecting patient function, and quality of life. The development of accurate and sensitive assessment tools for CIPN is essential to enable clinical monitoring during treatment, follow‐up of long‐term outcomes and measurement of toxicity in clinical trials. This review examines CIPN clinical assessment scales incorporating clinician‐based, composite, and patient‐reported outcomes (PROs), providing a systematic review of their properties and an updated critical analysis of recommendations on current evidence for their use. This systematic review of CIPN assessment tools identified 50 papers containing 41 assessment tools, across 4 categories (common toxicity criteria; composite neurological scale; PROs; pain scale). The majority of these tools were PROs, underscoring the importance of patient‐based assessment of symptoms. While there has been considerable work in the field over the past 10 years, this review highlights significant gaps, including a lack of evaluation of responsiveness and problematic neuropathic pain evaluation. There remains a need for consensus on the best available tool and the need to modify existing instruments to improve utility.